The Expansion of Firms - Rubin, Paul H. (Journal of Political Economy, 1973)
The firm is viewed as a collection of particular resources, that is, resources worth more to the firm than their market value because of specialized experience within the firm. Such resources can be used either for producing output or for training new resources. This assumption is incorporated into a programming model of the firm. This model is then used to derive predictive statements about the rate and direction of growth of the firm.